Decentering the self? Preliminary evidence for changes in self- vs. other related processing as a long-term outcome of loving-kindness meditation - Fynn-Mathis Trautwein; Fynn-Mathis Trautwein; José Raúl Naranjo; José Raúl Naranjo; Stefan Schmidt; Stefan Schmidt (Frontiers in Psychology, 2016)
AbstractResearch in social neuroscience provides increasing evidence that self and other are interconnected, both on a conceptual and on an affective representational level. Moreover, the ability to recognize the other as ‘like the self’ is thought to be essential for social phenomena like empathy and compassion. Meditation practices such as loving-kindness meditation (LKM) have been found to enhance these capacities. Therefore, we investigated whether LKM is associated to an increased integration of self-other-representations. As an indicator, we assessed the P300 event-related potential elicited by oddball stimuli of the self-face and a close other’s face in twelve long-term practitioners of LKM and twelve matched controls. In line with previous studies, the self elicited larger P300 amplitudes than close other. This effect was reduced in the meditation sample at parietal but not frontal midline sites. Within this group, smaller differences between self- and other-related P300 were associated with increasing meditation practice. Across groups, smaller P300 differences correlated with self-reported compassion. In meditators we also investigated the effect of a short LKM compared to a control priming procedure in order to test whether the state induction would additionally modulate self- versus other-related P300. However, no effect of the priming conditions was observed. Overall, our findings provide preliminary evidence that prolonged meditation practice may modulate self- versus other-related processing, accompanied by an increase in compassion. Further evidence is needed, however, to show if this is a direct outcome of loving-kindness meditation.